Changes in soil phosphorus dynamics amended with rock phosphate-enriched compost and chemical fertilizers - Dilkhush Meena; Murli Dhar Meena; Satendra Singh Sengar; Vidhya Nand Mishra; Anup Kumar; Mohan Lal Lakhera; Mohan Lal Dotaniya; Mukesh Kumar Meena; Sujith Kumar; Bheeru Lal Meena; Ram Swaroop Jat; Lalit Krishan Meena; et al. (PLoS ONE, 2025)
To adopt effective phosphorus (P) management strategies for sustainable mustard (Brassica juncea L.) production, it is crucial to understand how P is transformed and made available in the soil by utilising diverse P sources. In this study, a field experiment carried out with five treatment combinations; T1: control, T2:100% recommended dose of fertilizers (RDF), T3: enriched compost @ 6 t/ha, T4:100% RDF + enriched compost @ 6 t/ha, and T5:50% RDF + enriched compost @6 t/ha. Findings indicated that the soil treated with 100% RDF together with enhanced compost at 6 t/ha exhibited substantial improvements in saloid-P, aluminum-P (Al-P), iron-P (Fe-P) and calcium-P (Ca-P) in contrast to compost and 100% RDF alone; however, it was statistically similar to a treatment obtaining 50% RDF + enhanced compost @ 6 t/ha. For soil that has been fertilized with chemical fertilizers and enriched compost, remarkable improvement (15.5% and 8%) in alkaline phosphatase activity (ALPA) was seen in contrast to the exclusive use of chemical fertilizers and enriched compost, respectively, compared to 100% RDF, enriched compost and chemical fertilizers enhanced the amount of soil microbial biomass phosphorous (MBP; 55%), microbial biomass carbon (MBC; 34%), and dehydrogenase activity (DHA; 45%). Enriched compost @ 6 t/ha maintained greater P availability and microbial activities culminating in significantly higher mustard grain yield (2.93 Mg/ha). Mustard grain yield was 16.7% higher on soil treated with 100% RDF than control. The outcomes demonstrated that enrichment of processed compost (6 t/ha) with chemical fertilizers (100% RDF) is a good strategy for improved P accumulation deciphering P conversions in soil-plant systems and sustaining mustard yields in degraded ecosystems.